Evaluation of efficacy and toxicity of Interleukin 2 given subcutaneously in the treatment of disseminated renal cancer and malignant melanoma - Wiczyńska, Beata; Pawlicki, Marek; Ziobro, Marek; Zemełka, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2001)
Thirty patients with malignant melanoma or renal cancer were treated with Interleukin 2 given subcutaneously in Medical Oncology Department, Cancer Centre, Krakow-Branch in the period from January 1998 to June 1999. In the group of renal cancer two (11,1%) patients achieved a partial remission and 11 (61,1%) a stabilization of the disease lasting 10 and 8.8 month with survival time 12 and 12.2 month, respectively. Among patients with disseminated malignant melanoma two (16,7%) patients achieved complete remission and one patient (8,3%) partial remission of the disease lasted 10 and 12 month, respectively. Mean survival time was 16 and 19 month, respectively. Therapy was well tolerated, however, in 10% patients cardiovascular toxicity (hypotension) and renal toxicity (BUN and creatinine level elevation) were observed.